2013
DOI: 10.1260/1759-3131.4.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Teleconnections between Bangladesh Summer Monsoon Rainfall and Sea Surface Temperature in the Indian Ocean

Abstract: To explore the teleconnections between Bangladesh summer monsoon rainfall (BSMR) and sea surface temperature (SST) anomalies over different parts of the ocean have been examined from the years 1961-2008 (48-year). Global NCEP/NCAR reanalysis data of SST have been used at 2 degree by 2 degree grid in this study. A significant positive correlation (0.44) was found between the BSMR and SST over the southwest Indian Ocean (around 30 o S) in the month of February. All other monthly (January to May) correlations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
2
3
0
Order By: Relevance
“…For the positive IOD phase, a positive precipitation anomaly was found only in a narrow area near Cox's Bazar (Figure 12d-f). Such a weak response of precipitation to remote SST has been noted by previous studies [56,57,65]. Our composite analysis indicated that the passage of cyclones with a low SLP and high meridional wind enhances the SLA (Figure 7g).…”
Section: Influence Of Remote and Local Sstsupporting
confidence: 81%
See 1 more Smart Citation
“…For the positive IOD phase, a positive precipitation anomaly was found only in a narrow area near Cox's Bazar (Figure 12d-f). Such a weak response of precipitation to remote SST has been noted by previous studies [56,57,65]. Our composite analysis indicated that the passage of cyclones with a low SLP and high meridional wind enhances the SLA (Figure 7g).…”
Section: Influence Of Remote and Local Sstsupporting
confidence: 81%
“…It was found that the ESLs were influenced by the high precipitation during the monsoon season. The extreme sea levels intensify coastal inundation and cause coastal floods with high precipitation during monsoons [8,32,57,59,65]. Therefore, the attempt of this study relating to predictions of ESL has implications for the reduction of coastal hazards.…”
Section: Discussionmentioning
confidence: 99%
“…In observation, the ENSO-rainfall teleconnection is found to be positive although it is not statistically significant. Rahman et al (2013b) found the similar positive ENSO-rainfall teleconnection using observations from 1985 to 2008. In contrast, the ENSO-rainfall teleconnections in most of the GCMs indicate a strongly negative relationship, indicating that GCMs are unable to reproduce the observed teleconnections satisfactorily, even of an opposite sign.…”
Section: Skill Of Uncalibrated Gcm Predictionssupporting
confidence: 69%
“…ARIMA models have been used to predict rainfall with lead times of up to 12 months (Mahmud et al, 2017), but the lack of statistical significance of year‐to‐year autocorrelation can lead to limited forecasting skills (Dahale & Singh, 1993). A more widely‐used approach has been the use of empirical relationships between observed BSMR and predictors such as sea‐surface temperature, surface air temperature and pressure gradients (Hossain et al, 2019; Rahman et al, 2013b). For instance, the prediction of the monthly and seasonal frequency of rainy days and heavy rainfall events have been attempted using SST as a predictor (Mannan et al, 2015), and skill is higher than for the monsoon seasonal total amount, consistent with results from other parts of the world (Robertson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature gradient between the Indian Ocean and Tibetan Plateau plays a critical role in the inter-annual variability of the South Asian monsoon. All these factors regulate the regional climatic difference over Bangladesh [9][10][11].…”
Section: General Characteristics Of Bangladesh Climatementioning
confidence: 99%